2009
DOI: 10.1016/j.jsmc.2009.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Circadian System on Disease Severity

Abstract: SynopsisThe severity of many diseases varies across the day and night. For example, adverse cardiovascular incidents peak in the morning, asthma is often worse at night and temporal lobe epileptic seizures are most prevalent in the afternoon. These patterns may be due to the day/night rhythm in environment and behavior, and/or endogenous circadian rhythms in physiology. Furthermore, chronic misalignment between the endogenous circadian timing system and the behavioral cycles could be a cause of increased risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 209 publications
(188 reference statements)
0
57
0
Order By: Relevance
“…Epidemiological evidence of day/night patterns in disease severity suggests interacting roles of behavioural triggers and endogenous circadian systems [1]. Circadian misalignment has been implicated in the development of obesity, insulin resistance, diabetes mellitus, and cardiovascular disease [1].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological evidence of day/night patterns in disease severity suggests interacting roles of behavioural triggers and endogenous circadian systems [1]. Circadian misalignment has been implicated in the development of obesity, insulin resistance, diabetes mellitus, and cardiovascular disease [1].…”
Section: Introductionmentioning
confidence: 99%
“…Asthma shares a lot of characteristics with allergic diseases, including genetic risk factors (Bousquet et al 2000). Asthma episodes, as well as asthma exacerbations, are more prone to happen during the night and early morning compared to other times of the day both in adults and in children (Smolensky et al 2007;Reinberg et al 1988;Turner-Warwick 1988;Smolensky and D'Alonzo 1997;Hoskyns et al 1995;Jarjour 1999;Bohadana et al 2002;Litinski et al 2009). One of the first studies involving 3000 asthma patients found that asthma episodes during washout from regular maintenance asthma treatment occurred 70-fold more frequently between 4 am and 5 am compared to 2 pm-3 pm (Dethlefsen and Repges 1985).…”
Section: Asthmamentioning
confidence: 99%
“…It has been recognized that circadian rhythms performs an important role in certain disease states as these disease states have chronological aspects related to them (108). One such example is asthma which has shown to become formidable in the early hours of morning (2-8 am) when most patients are asleep (108).…”
Section: Chronotherapeutism From Polymer Refabricationmentioning
confidence: 99%